High Prevalence of Azithromycin-Resistant Neisseria gonorrhoeae Isolates With a Multidrug Resistance Phenotype in Fukuoka, Japan. Issue 6 (June 2015) - Tanaka, Masatoshi; Furuya, Ryusaburo; Irie, Shinichiro; Kanayama, Akiko; Kobayashi, Intetsu
<x xml:space="preserve">Abstract</x> Background The current guidelines recommend a combination of ceftriaxone and azithromycin as a first-line treatment of gonorrhea in the United States and Europe. Despite not being recommended as a first-line regimen in Japan, an oral 2-g dose of azithromycin did become available for gonococcal infections in 2009. Recently, the emergence of azithromycin-resistant Neisseria gonorrhoeae isolates has been reported in several countries, including Japan. Methods Antimicrobial susceptibility testing was performed on a total of 677 clinical isolates of N. gonorrhoeae obtained from January 2010 to December 2013 in Fukuoka, Japan. A molecular analysis by N. gonorrhoeae multiantigen sequence typing was conducted on the azithromycin-resistant isolates. Results The proportion of azithromycin-resistant isolates (minimum inhibitory concentration > 0.5 μg/mL) increased significantly from 1.8% in 2010 to 22.6% in 2013 (P < 0.001). Among 50 azithromycin-resistant isolates, 30 (60%) exhibited a resistant phenotype to multiple drugs including cefixime. The 2 predominant sequence types (STs) identified by N. gonorrhoeae multiantigen sequence typing were ST6798 (por allele 4033 and tbpB allele 110) and ST1407 (por allele 908 and tbpB allele 110) at 40.0% (20/50) and 12.0% (6/50), respectively. There was a statistically significant increase of the proportion of ST6798 from 0% (0/19) in 2010–2012 to 64.5% (20/31) in 2013 (P < 0.001). Conclusions Over the previous 4 years, an increasing prevalence of azithromycin-resistant N. gonorrhoeae isolates with a multidrug-resistant phenotype was observed. Furthermore, the azithromycin-resistant isolates seemed to belong to 2 predominant STs. As a result, continued surveillance of gonococci resistant to antimicrobial agents, including azithromycin in Fukuoka, Japan, is necessary.